Advancing STEM-Based Business Sustainability: Mending the Curricular Gap. (March 2020) - Petrun Sayers, Elizabeth L.; Craig, Christopher A.; Gilbertz, Susan; Feng, Song; Karam, Rita T.; Bohman, Angelena
Businesses are increasingly facing economic, social, and environmental sustainability challenges. Science, technology, engineering, and math (STEM) are needed to address business sustainability needs, yet such competencies are noticeably absent from academic literature and business curricula. To mend the curricular gap, we make the case for developing cross-disciplinary STEM-based business sustainability curricula that enhance students' sustainability literacy and cognitive abilities related to STEM and sustainability. A literature review is provided that documents curricular gaps specific to STEM and sustainability in the academic literature and in business sustainability program offerings. We then present a framework that can be used to integrate STEM and sustainability across the curricula and to evaluate curricular implementation. This review provides timely and relevant information that can help business management educators, instructors, and administrators justify, design, develop, implement, and evaluate STEM-based business sustainability curricula.